(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Well-being is the biggest and most important goal of human being life that affects a person's health more than anything else does. This study aimed to investigate the role of mindfulness and its dimensions in students' psychological well-being. Methods: The research method was correlation and the statistical population included all students of Kharazmi University. The sample consisted of 240 students (126 females and 114 males) who were selected by the convenience sampling method. The research instruments were the Five Facet Mindfulness Questionnaire (FFMQ) (Bauer et al. 2006) and Ryff's scale of the Psychological Well-Being (Ryff, 1980). Data analysis was performed using independent groups of t-test, Pearson correlation coefficient, and stepwise regression. Results: The obtained results showed that there is no significant difference between male and female students in the variables of mindfulness and psychological well-being. There is a positive and significant correlation between psychological well-being and the overall score of mindfulness as well as the dimensions of observing, describing, acting with awareness, and non-reactive. Conclusions: The variables of acting with awareness and describing mindfulness dimensions were able to explain about 24% of the variance of psychological well-being in two steps. Keywords: Mindfulness, Psychological well-being, Students